Impact of sleep disordered breathing on performance in judo players. Issue 1 (24th April 2019) - Wada, Hiroo; Nagata, Kazumasa; Shirahama, Ryutaro; Tajima, Tomokazu; Kimura, Manami; Ikeda, Ai; Maruyama, Koutatsu; Tamura, Masahiro; Suzuki, Keiji; Tanigawa, Takeshi
Abstract : Objective: Previous studies have suggested that young sports players may suffer from sleep disordered breathing (SDB). It was hypothesised that SDB in heavy-class judo players was far more prevalent than expected and that it could reduce judo performance, which could be improved by appropriate therapies. To address this, the present study estimated the percentage of heavy-class judo players with SDB and investigated the effect of SDB treatment on judo performance. Methods: We enrolled 19 young judo players from a university judo team with body weight >100 kg and/or body mass index >30 kg/m 2 . Both excessive daytime sleepiness (EDS) and respiratory disturbance index (RDI) were evaluated using the Epworth Sleepiness Scale (ESS) and an overnight type 3 sleep monitor. Results: The percentages of young heavyweight-class judo players with EDS (ESS ≥11) and those with SDB (RDI ≥5) were both 63%, which was unexpectedly high for the age class. Seven of the participants underwent continuous positive airway pressure therapy, which improved both RDI and ESS scores (p<0.05 for each) and subsequently the sleep quality and judo performance of the participants. Conclusions: Our study indicates that young judo players might silently suffer from SDB, leading to poorer judo performance and to future cardiovascular diseases. Clinicians should be aware of the possible presence of SDB in young sports players and consider the application of diagnostic and therapeutic remedies.